PREVENTING NON-COMMUNICABLE DISEASES IN TOURIST SITES THROUGH HEALTHY CANTEEN MANAGEMENT - Mahendro Prasetyo Kusumo; Kusbaryanto Kusbaryanto; Muhammad Eko Atmojo (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2021)
Background: Cadre involvement is important to increase public knowledge and awareness of diet control. Dietary control contributes to the reduction in the prevalence of NCDs. Objective: To explore the involvement of cadres in improving dietary control behavior to control NCDs. Methods: This community service was carried out in Sendangtirto Village, Berbah District, Sleman Regency Yogyakarta. Qualitative method with action research design used to explore the involvement of cadres in implementing diet. The selection of participants was purposive sampling. Data was collected using interview, FGD, and observation techniques. Triangulation and member checking are carried out to validate the resulting data. The data processing process begins with transcription, open coding, axial coding and the preparation of themes. Data were analyzed using NVivo software. Results and implication: The qualitative data analysis concluded that there were five themes, namely: 1) the purpose of implementing a diet, 2) a model of implementing a diet based on cadre empowerment, 3) obstacles to implementing a diet, 4) efforts to improve the implementation of a diet, and 5) efforts in NCDs control. Implications: Empowerment of cadres is one form of activity that can increase the active role of the community in healthy behavior. This active role encourages people to be more active in conveying their personal experiences in controlling their eating patterns. Conclusion: Empowerment of cadres increases the active role of the community in controlling diet to control